Pengaruh Infeksi Kecacingan terhadap Kadar Hemoglobin pada Remaja Putri dengan Anemia - DWI RAHAYU (Faculty of Medicine Universitas Sebelas Maret, 2018)
Introduction: Anemia is one of the health problems in Indonesian. The government has launched anemia prevention programs, including for young women, but the prevalence of anemia is still high. Helminth infections can decrease hemoglobin (Hb) levels through gastrointestinal bleeding and decreased food intake. This study aimed to determine the effect of helminth infections on Hb levels in young women.Methods: This study was an observational analytic study with a case control approach. Research subject involved of 46 students of senior high school in Sukoharjo Regency and were divided into 26 young women with anemia and 20 young women without anemia. Helminth infection was determined using fecal examination. All collected data were analyzed by Chi square test and Independent sample t-test with p<0.05.Results: The mean of Hb levels in young women with anemia was 10.24±0.92g/dL and the mean of Hb levels in young women without anemia was 13.07±0.44g/dL. 7 young women suffered helminth infection, divided into 2 young women with anemia and 5 young women without anemia. However, there was not statistically significant relationship between helminth infection and anemia (p=0.11). The mean of Hb levels in young women with helminth infection were higher both those who suffered anemia (11.30± 0.56 g /dL) or not (13.08 ± 0.42g /dL) compared with Hb levels in young women without helminth infection (anemia 10.37±1.06g/dL; not anemia 11.34±1.52g/dL).Conclusion: Helminth infection was not related to the incidence of anemia in young women even though Hb levels in helminth infections were higher compared to Hb levels without helminth infections.